The Anti-Corruption Legal Revolution: Updates to the Latest Laws in 2025 - Hana, Bella Suspia; Mukhlis, Mukhlis (Mandalika Law Journal, 2025)
This study provides a comprehensive analysis of the anti-corruption law landscape in Indonesia during 2025, a year characterized by significant legislative dynamics and judicial reviews rather than the enactment of a new, comprehensive anti-corruption act. The primary legal framework remains Law No. 31/1999 juncto Law No. 20/2001. A pivotal development in 2025 was the controversial implementation of Law No. 1/2025 on State-Owned Enterprises (SOEs), which reclassified SOE directors and commissioners as non-state officials. This change, coupled with the formalistic implementation of the 2025 Presidential Regulation on Procurement (Perpres PBJ), potentially limits the jurisdiction of the Corruption Eradication Commission (KPK) and the State Audit Body (BPK), creating significant legal uncertainty. The research uses qualitative legislative analysis to argue that the "revolution" in 2025 is not defined by a new comprehensive law, but by the strategic weakening of enforcement mechanisms in specific strategic sectors, alongside ongoing judicial review processes at the Constitutional Court regarding existing anti-corruption articles, and the influence of the post-election 2024 political regime. The conclusion suggests these changes pose complex challenges to the national anti-corruption framework and may signal a step backward in governance accountability.